Twists of the Visible in "A emparedada da Rua Nova" by E Theater and Dance Company and "This is my Body" by Janet Toro (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article investigates the temporal and spatial disagreements between the immediate and shared act of performance exhibition and observation, more common in theory. To do so, it analyzes the works "A emparedada da Rua Nova" (2017) by E² Theater and Dance Company and "This is my Body" (2019) by Janet Toro, which choose to invert the usual visibility relationships in performance. Through them, it is demonstrated how both deal with violence not merely as a theme, but as a constituent of the work through twists of what is made visible to the audience, which precisely surpasses an affirmative relationship of performative demonstration and calls the audience to a reflective experience of theoretical order.
Keywords: violence; performance; theory